IMMUNOCHEMICAL STUDY OF ANTIGENIC SPECIFICITY IN DELAYED HYPERSENSITIVITY : V. IMMUNIZATION WITH MONOVALENT LOW MOLECULAR WEIGHT CONJUGATES - Leskowitz, Sidney (The Rockefeller University Press, 1966)
Hapten-specific delayed hypersensitivity was produced by immunization of guinea pigs with arsanilic acid conjugated to N-acetyltyrosine or other small aromatic molecules. Such hapten-specific delayed sensitivity could be passively transferred by peritoneal exudate cells. While a conjugate made from a polymer of D-amino acids was ineffective in producing sensitization, the conjugate made with D-tyrosine was effective, suggesting that the inability of D-amino acid polymers to be broken down by enzymes might be bypassed by use of the monomer. The effectiveness of such monomers in producing delayed sensitivity, but not antibody production, is consistent with a hypothesis that different types of antigenic determinants are involved in the production of each.